THE CAPE VERDEAN SLUM AREAS IN PORTUGAL, INTEGRATION OR SEGREGATION? HOW DOES THE SCHOOL PREPARE THE YOUNG CAPE VERDEAN IMMIGRANT GENERATION TO INTEGRATION IN THE PORTUGUESE SOCIETY? - Lea, Martha (European Scientific Journal, ESJ, 2014)
Children do not ask for immigration. Tests show that immigrant students do less well than native students at school. Have their future possibilities become worse, while their parents wanted to get better conditions? How does school enhance their capacity to be equalised with native co-students? According to a Canadian professor, Jim Cummins, the way to go is to respect their mother tongue, their cultural identity and values and build upon this as a fundament for further education in cooperation with their parents and in an open communication between teachers and students .Is this the way to go to give the immigrant Cape Verde youth in the slum areas in Lisbon a starting point for a better future?